FAKTOR – FAKTOR YANG MEMENGARUHI DIVIDEND POLICY PADA PERUSAHAAN CONSUMER GOODS - Liem, Catrina; Salim, Susanto (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
This study was conducted to determine the effect of free cash flow, firm size, current ratio, and return on equity to Dividend Policy on consumer goods companies listed on the Indonesia Stock Exchange during the period 2017-2020. The sample used in this study were 20 companies using purposive sampling technique. Valid data is as much as 80 data. This study performs data processing using the Eviews for Windows version 12 program and the data collection process using Microsoft Excel 2010. The results of the analysis show that the free cash flow, current ratio and return on equity variabels have a positive and significant effect on dividend policy, while the firm size variabel does not effect on dividend policy.